Improving year 1 pupils understanding of short vowel sounds /e/ and /æ/ by using Talking Pipes With Stavira Automated Phoneme Transcriptions (TPAPT) / Shaheen Amirun Amsyar Shahridzuan ... [et al.] - Shahridzuan, Shaheen Amirun Amsyar; Muhammad Hafiz, Faheem Haiqal; Khairul Hakimin, Khairul Muadz Muhaimin; Mohd Hasrul, Mohammad Harith Adam; Setapa, Mohd Saharudin (2020)
Talking Pipes with Stavira Automated Phoneme Transcriptions (TPAPT) is an innovation on enhancing year 1 pupils understanding between short vowel sounds /e/ and /æ/ as to improve their speaking skill. Pupils frequently confuse pronouncing words with /e/ and /æ/ sounds like 'met' and 'mat' and 'dead' and 'dad'. Mispronunciation of words using /e/ and /æ/ sounds usually happens because the sounds is almost the same. This innovation aimed to identify the effectiveness of TPAPT and pupils' interest in practicing /e/ and /æ/ sounds using TPAPT. Three stages are introduced in the process of using TPAPT where first participants are required to distinguish the /e/ and /æ/ sounds based on the information explained in the Stavira application. Second, recognize the sounds by using adjustable talking pipes and third, test their understanding of /e/ and /æ/ sounds using the automated phoneme transcriptions. After one cycle of using TPAPT, participants were able to differentiate between /e/ and /æ/ sounds and they like the innovation. As a conclusion, TPAPT enable pupils to reduce errors and can improve their understanding of /e/ and /æ/ sounds. This innovation can be furthered by combining other phoneme sounds in one practice since the tools can be applied to all phoneme sounds.